2017
DOI: 10.1097/mjt.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of a Pharmacy-Led Blood Factor Stewardship Program

Abstract: To report the results of a pharmacist-directed blood factor stewardship program targeting off-label utilization designed to limit use to established organizational guidelines in high-risk populations. Prospective evaluation of recombinant factor VIIa and prothrombin complex concentrate orders beginning June 2013 through May 2014 and a matched retrospective cohort from June 2012 to May 2013. Matched cohorts were evaluated for 28-day mortality, change in international normalized ratio (INR), adverse events, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…During times of shortage, institutions may consider restricting PCC4 to patients requiring reversal of vitamin K antagonists for major bleeding or emergent surgery and using alternative agents for off-label indications (e.g., reversal of direct acting oral anticoagulants, major bleeding during cardiac surgery, and treatment of coagulopathy secondary to liver dysfunction). A prospective blood factor stewardship program has been shown to reduce inappropriate use of PCC4 [33,34].…”
Section: Prothrombin Complex Concentratementioning
confidence: 99%
“…During times of shortage, institutions may consider restricting PCC4 to patients requiring reversal of vitamin K antagonists for major bleeding or emergent surgery and using alternative agents for off-label indications (e.g., reversal of direct acting oral anticoagulants, major bleeding during cardiac surgery, and treatment of coagulopathy secondary to liver dysfunction). A prospective blood factor stewardship program has been shown to reduce inappropriate use of PCC4 [33,34].…”
Section: Prothrombin Complex Concentratementioning
confidence: 99%
“…15 In addition, Trueg et al conducted an evaluation of rFVIIa and PCC orders before and after implementation of a pharmacist-directed blood factor stewardship program. 19 Mortality at 28 days was similar between groups (53.9% versus 50%, p = 0.77); however, there was an annual cost savings of $375,539, primarily through a significant reduction in rFVIIa utilization. 19 Similar to these studies, we found a decrease in rFVIIa administered with the implementation of an off-label dosing guideline, leading to a $414,500 decrease in the annual costs of rFVIIa.…”
Section: Discussionmentioning
confidence: 80%
“…19 Mortality at 28 days was similar between groups (53.9% versus 50%, p = 0.77); however, there was an annual cost savings of $375,539, primarily through a significant reduction in rFVIIa utilization. 19 Similar to these studies, we found a decrease in rFVIIa administered with the implementation of an off-label dosing guideline, leading to a $414,500 decrease in the annual costs of rFVIIa. This may have been attributed to the recommendation for lower initial starting doses, the use of dose rounding, and purchasing multiple vial strengths to limit waste.…”
Section: Discussionmentioning
confidence: 80%
“…Emergency anticoagulation reversal involves using an appropriate reversal agent at an appropriate dose in response to either a life‐threatening bleed or for an emergency procedure. A retrospective cohort evaluated the impact of a pharmacist‐led blood factor stewardship program and found that total CA during 1 year was $375,539, amounting to $8941.40 per patient . A similar study found that a pharmacist working with a hematologist resulted in an annual savings of more than $4 million in blood factor stewardship .…”
Section: Results Of Scoping Reviewmentioning
confidence: 99%
“…A retrospective cohort evaluated the impact of a pharmacist-led blood factor stewardship program and found that total CA during 1 year was $375,539, amounting to $8941.40 per patient. 69 A similar study found that a pharmacist working with a hematologist resulted in an annual savings of more than $4 million in blood factor stewardship. 70 The actual cost savings for specific types of interventions were not provided.…”
Section: Blood Factor Stewardship and Emergency Anticoagulation Revermentioning
confidence: 94%